The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12890-021-01585-5
|View full text |Cite
|
Sign up to set email alerts
|

Secondary polycythemia in chronic obstructive pulmonary disease: prevalence and risk factors

Abstract: Background Secondary polycythemia is associated with cigarette smoking and chronic obstructive pulmonary disease (COPD). However, the prevalence of polycythemia in COPD and the contributing risk factors for polycythemia in COPD have not been extensively studied. Methods We analyzed the presence of secondary polycythemia in current and former smokers with moderate to very severe COPD at the five-year follow-up visit in the observational COPDGene stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
28
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 63 publications
(65 reference statements)
7
28
2
Order By: Relevance
“…4 Zhang et al found that 6.6% of COPD patients met the diagnostic criteria for polycythemia with a cutoff of Hb >165 g/L in males and >160 g/L in females and suggested that race and altitude have an impact on the prevalence of polycythemia. 20 In our study, the prevalence of polycythemia was only 3.9%, which might be because all our patients lived at high altitudes and ethnic groups other than Han were excluded.…”
Section: Discussionmentioning
confidence: 67%
“…4 Zhang et al found that 6.6% of COPD patients met the diagnostic criteria for polycythemia with a cutoff of Hb >165 g/L in males and >160 g/L in females and suggested that race and altitude have an impact on the prevalence of polycythemia. 20 In our study, the prevalence of polycythemia was only 3.9%, which might be because all our patients lived at high altitudes and ethnic groups other than Han were excluded.…”
Section: Discussionmentioning
confidence: 67%
“…Previous studies have revealed that physiologic reaction to excitement, splenic contraction, or inflammatory response could increase reticulocyte numbers in non-anemic conditions [7][8][9]. In addition, there have been many studies about hypoxic RAA [6,[10][11][12]. Some studies have shown that patients with RAA have poorer prognosis [6,12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there have been many studies about hypoxic RAA [6,[10][11][12]. Some studies have shown that patients with RAA have poorer prognosis [6,12]. In light of the growing interest in RAA, the study of hypoxic RAA in specific diseases would be a substantial contribution to the field of veterinary medicine [7,13].…”
Section: Introductionmentioning
confidence: 99%
“… 19 , 29 However, although some patients with COPD presented with marked polycythemia, other COPD patients had no or only a mild concurrent increase in red blood cell parameters. 30 , 31 In our study, because CIPF dogs all were WHWTs, it is impossible to differentiate whether the lack of erythrocytosis was associated with the disease process itself or a breed‐related genetic response to hypoxemia.…”
Section: Discussionmentioning
confidence: 81%